Novel Development and Sensory Evaluation of Extruded Snacks from Unripe Banana (Musa ABB cv. Kluai ‘Namwa’) and Rice Flour Enriched with Antioxidant-Rich Curcuma longa Microcapsules - Nurulhusna Awaeloh; Surasak Limsuwan; Pinanong Na-Phatthalung; Thammarat Kaewmanee; Sasitorn Chusri (Foods)
With the growing consumer demand for natural functional ingredients that promote health and well-being while preventing age-related diseases, this study aimed to develop extruded snacks enriched with Curcuma longa (turmeric) microcapsules, recognized for their significant antioxidant properties. Unripe banana flour (Musa ABB cv. Kluai ‘Namwa’) and rice (Oryza sativa) flour were employed as a gluten-free base to create this novel extruded snack. Curcuma longa extract microcapsules were prepared using a spray-drying technique with varying core-to-wall ratios. Antioxidant capacities were assessed through DPPH, ABTS, superoxide radical scavenging, metal chelating, and ferric-reducing assays. The CM6 microcapsules, prepared at 140 °C with a 1:10 core-to-wall ratio, exhibited potent antioxidant activity, with 58.93 ± 3.31% inhibition for DPPH radicals, 87.58 ± 1.33% for ABTS, and 78.41 ± 1.40% for superoxide radicals. Snacks enriched with 0.25% CM6 microcapsules received high consumer acceptance, with an average liking score of 7.5 out of 9. These findings suggest that snacks made with these gluten-free flours and Curcuma longa microcapsules could be novel, convenient, and appealing functional food products that offer an attractive way to deliver antioxidant benefits with high consumer acceptance. Further research on evaluating the active constituents in the snack, its long-term health benefits, and shelf-life stability is recommended for commercialization.